2017
DOI: 10.1186/s12986-017-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolites in non-alcoholic fatty-liver disease development or reversion; a targeted metabolomic approach within the PREDIMED trial

Abstract: Background Limited prospective studies have examined changes in non-alcoholic fatty-liver disease (NAFLD) related serum-metabolites and none the effects of NAFLD-reversion. We aimed to evaluate whether perturbations in metabolites indicate predisposition to NAFLD development and to assess the effects of NAFLD reversion on metabolite profiles.MethodsA targeted liquid-chromatography tandem mass-spectrometry metabolic profiling (n = 453 metabolites) approach was applied, using serum from 45 subjects of the PREDIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
2
20
0
1
Order By: Relevance
“…Recent studies demonstrated that LPCATs may also contribute to the pathogenesis of NAFLD. Attempts to identify diagnostic markers of NAFLD have found that serum lysoPC levels are decreased in NASH patients (116)(117)(118). Similar decreases in serum lysoPC levels were observed in a mouse NASH model induced by a methionine-and choline-deficient (MCD) diet (119).…”
Section: Lpcats In Nonalcoholic Fatty Liver Diseasementioning
confidence: 83%
“…Recent studies demonstrated that LPCATs may also contribute to the pathogenesis of NAFLD. Attempts to identify diagnostic markers of NAFLD have found that serum lysoPC levels are decreased in NASH patients (116)(117)(118). Similar decreases in serum lysoPC levels were observed in a mouse NASH model induced by a methionine-and choline-deficient (MCD) diet (119).…”
Section: Lpcats In Nonalcoholic Fatty Liver Diseasementioning
confidence: 83%
“…(all in serum) [241] [228] [240] Overall Summary A summary of metabolic, metabolomic, and lipidomic investigations into ALD is given in Table 1. It is clear that the hepatic metabolic phenotypes and therefore biomarkers of both chronic alcohol consumption and ALD are far from being defined.…”
Section: Uplc-qtofmsmentioning
confidence: 99%
“…Papandreou et al [ 21 ] analyzed the rearrangement of lipid biosynthesis occurring in patients with non-alcoholic liver steatosis with a follow-up period of 3.8 years. They subdivided 45 patients into the following subgroups: (1) HC; (2) liver steatosis; (3) liver steatosis reversion during the follow-up.…”
Section: Metabolic Alterations Of Nafldmentioning
confidence: 99%